Antiepileptic Effects of Lacosamide Loaded Polymers Implanted Subdurally in GAERS. (20th January 2016) - Bauquier, Sebastien H.; Jiang, Jonathan L.; Yue, Zhilian; Lai, Alan; Chen, Yu; Moulton, Simon E.; McLean, Karen J.; Vogrin, Sara; Halliday, Amy J.; Wallace, Gordon; Cook, Mark J.
Abstract : The current experiment investigated the ability of coaxial electrospun poly(D, L-lactide-co-glycolide) (PLGA) biodegradable polymer implants loaded with the antiepileptic drugs (AED) lacosamide to reduce seizures following implantation above the motor cortex in the Genetic Absence Epilepsy Rat from Strasbourg (GAERS). In this prospective, randomized, masked experiments, GAERS underwent surgery for implantation of skull electrodes (n = 6 ), skull electrodes and blank polymers (n = 6 ), or skull electrodes and lacosamide loaded polymers (n = 6 ). Thirty-minute electroencephalogram (EEG) recordings were started at day 7 after surgery and continued for eight weeks. The number of SWDs and mean duration of one SWD were compared week-by-week between the three groups. There was no difference in the number of SWDs between any of the groups. However, the mean duration of one SWD was significantly lower in the lacosamide polymer group for up to 7 weeks when compared to the control group (0.004 < p < 0.038 ). The mean duration of one seizure was also lower at weeks 3, 5, 6, and 7 when compared to the blank polymer group (p = 0.016, 0.037, 0.025, and 0.025, resp.). We have demonstrated that AED loaded PLGA polymer sheets implanted on the surface of the cortex could affect seizure activity in GAERS for a sustained period.